PERBEDAAN EFEKTIVITAS DESINFEKSI INSTRUMEN KACA MULUT DENGAN PERENDAMAN ALKOHOL 70% DAN PENGUSAPAN ALKOHOL 70% TERHADAP PENURUNAN JUMLAH BAKTERI PADA KACA MULUT - Yasmine Auliya Rahma; Ida Rahmawati; Siti Sab’atul Habibah (Poltekkes Kemenkes Banjarmasin, 2021)
Dental health workers are susceptible to cross-infection, one of which is through instruments, for example, mouth mirrors. So it is necessary to control cross-infection, for example using disinfection. 70% alcohol is an intermediate-level disinfectant. In this study, soaking the mouthpiece in 70% alcohol was done by immersing the mouthpiece into a container filled with 70% alcohol, while for 70% alcohol swab it was done by wetting a sterile cotton swab with 70% alcohol solution and then wiping it on the mouthpiece for 1 minute. This study was conducted to determine the difference in the effectiveness of the disinfection of mouthpiece instruments with 70% alcohol immersion and 70% alcohol rubbing on the decrease in the number of bacteria on the mouthpiece. The type of research is quasi-experimental, the research design is Two Group Pre-Post Test Design and the sampling is purposive sampling with a sample of 20 mouth mirrors that have been used. The results showed the effectiveness of the disinfection of mouth mirror instruments with 70% alcohol immersion to decrease the number of bacteria by 62%, the effectiveness of the disinfection of mouth mirror instruments by rubbing alcohol 70% on decreasing the number of bacteria by 90%. From the test, the Mann Whitney difference in the effectiveness of the disinfection of mouth mirror instruments with 70% alcohol immersion and 70% rubbing on the number of bacteria on the mouthpiece stated that P-value = 0.597, meaning p > (0.05) (Ho is accepted and Ha is rejected). In conclusion, there is no significant difference between disinfection of mouthpiece instruments with 70% alcohol immersion and 70% alcohol rubbing on the decrease in the number of bacteria on the mouthpiece. It is recommended that during the disinfection process, factors that can affect and asepticism be paid more attention to to help reduce the risk of cross-infection. Keywords: Effectiveness of Disinfection, Alcohol 70%